Performance and safety of an integrated bihormonal artificial pancreas for fully automated glucose control at home - Blauw, H. (Diabetes Obes Metab, 2016)
AIMS: To assess the performance and safety of an integrated bihormonal artificial pancreas system consisting of one wearable device and two wireless glucose sensor transmitters during short‐term daily use at home. METHODS: Adult patients with type 1 diabetes using an insulin pump were invited to enrol in this randomized crossover study. Treatment with the artificial pancreas started with a day and night in the clinical research centre, followed by 3 days at home. The control period consisted of 4 days of insulin pump therapy at home with blinded continuous glucose monitoring for data collection. Days 2–4 were predefined as the analysis period, with median glucose as the primary outcome. RESULTS: A total of 10 patients completed the study. The median [interquartile range (IQR)] glucose level was similar for the two treatments [7.3 (7.0–7.6) mmol/l for the artificial pancreas vs. 7.7 (7.0–9.0) mmol/l for the control; p = 0.123]. The median (IQR) percentage of time spent in euglycaemia (3.9–10 mmol/l) was longer during use of the artificial pancreas [84.7 (82.2–87.8)% for the artificial pancreas vs. 68.5 (57.9–83.6)% for the control; p = 0.007]. Time in hypoglycaemia was 1.3 (0.2–3.2)% for the artificial pancreas and 2.4 (0.4–10.3)% for the control treatment (p = 0.139). Separate analysis of daytime and night‐time showed that the improvements were mainly achieved during the night. CONCLUSIONS: The results of this pilot study suggest that our integrated artificial pancreas provides better glucose control than insulin pump therapy in patients with type 1 diabetes at home and that the treatment is safe.